Customer Service Strategies for Building Loyalty and Satisfaction at The Heights Sky Lounge - Amirullah, Faizal; Wijoyo, Tuwuh Adhistyo (Manunggal Halim Jaya, 2025)
This research examines the influence of customer service practices on improving visitor loyalty and satisfaction at The Heights Sky Lounge. The study utilizes a qualitative research methodology to investigate the influential aspects of customer experiences. This is achieved via the use of in-depth interviews, focus groups, observational research, and document analysis. The results indicate that providing tailored service, comprehensive staff training, meticulous attention to detail, and strong feedback systems are essential for enhancing customer happiness and cultivating loyalty. Customized interactions and individualized suggestions greatly improve the eating experience, while proficient personnel guarantee constant and top-notch service. The careful consideration of the physical setting and eating mood enhances the whole experience, making it more memorable. Moreover, the proficient use of client input enables ongoing improvement and adjustment to changing tastes. While the present service procedures generally meet consumer expectations, there are areas where improvements may be made in terms of providing consistent customized care and being adaptable to individual demands. This study offers useful insights for improving customer service tactics to enhance loyalty and achieve long-term success in the highly competitive premium dining industry.